Implikasi Pengisian Jabatan Tinggi Pratama Terhadap Pelaksanaan Putusan Pengadilan Tata Usaha Negara Akibat Pemberhentian Pejabat Tinggi Oleh Pejabat Pembina Kepegawaian - Khairani, Khairani; Gusminarti, Gusminarti; Qadri, Muhammad (Faculty of Law, Andalas University, 2023)
This study aims to find a solution or policy in the case of the termination of the Senior High Officials (Regional Secretary of West Pasaman Regency) by Civil Service Officers (Regent of West Pasaman Regency). The Regional Secretary of West Pasaman Regency who was terminated then filed a lawsuit to Padang Administrative Court (PTUN Padang) which court stating that the decision that termination was invalid, so the Terminated Official had the right to be reinstated. The court decision could not be implemented and came to a dead end because the position had also been filled by another Official (the new Regional Secretary of West Pasaman Regency) by the merit system according to the State Civil Apparatus Law (ASN Law) which was elected by the Committee. The selection of the leaders of the Primary High Offices are based on the recommendations of the State Civilian Bureaucracy Commission (KASN). This research was conducted using a sociologic and juridical method that analyzes the application of laws and regulations. The results showed that the termination of the Regional Secretary of West Pasaman Regency in terms of authority was in accordance with the regulations but in terms of procedural the Regent did not follow the provisions contained in the Civil Servant Discipline Regulation because the tenure of the regional secretary was less than 2 years without any summons, but immediately issued a Termination Letter based on the recommendation from the Inspectorate and the Governor of West Sumatra. Implications of the reappointment of Manus Handri as regional secretary based on the court decision which states that the termination of the regional secretary is illegal, but cannot be implemented because the new regional secretary has been elected based on KASN recommendations during the process of resolving Manus Handri's lawsuit at court. Termination and reinstated are difficult to be implemented because there are unclear provisions on how long the Human Resources Officer can reinstate terminated Officials who submit their cases to the Court. Therefore, there must be clear provisions in Law Number 30 Year 2014 and / or in Law Number 5 Year 1986 concerning the position of Officials who challenge the Decree on Transfer or termination during the trial process until the court's decision has permanent legal force. There should be a clause so that the Civil Service Officer (PPK) does not fill a new official with a position that is currently being processed in court.